1995
DOI: 10.1148/radiology.194.3.7862972
|View full text |Cite
|
Sign up to set email alerts
|

Strecker stent implantation in iliac arteries: patency and predictive factors for long-term success.

Abstract: Use of the Strecker endoprosthesis appears useful but not ideal. Determination of predictive factors for long-term success may help identify indications for its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…Previous studies have compared different types of BMSs deployed in iliac arteries and failed to demonstrate any significant differences in technical success and follow-up outcomes. [25][26][27] The only published randomized study comparing primary angioplasty, followed by selective or primary stent placement in patients with iliac artery obstructive disease, is the Dutch Iliac Stent Trial (DIST). The short-term and long-term DIST results indicated that selective stent placement should be considered as the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared different types of BMSs deployed in iliac arteries and failed to demonstrate any significant differences in technical success and follow-up outcomes. [25][26][27] The only published randomized study comparing primary angioplasty, followed by selective or primary stent placement in patients with iliac artery obstructive disease, is the Dutch Iliac Stent Trial (DIST). The short-term and long-term DIST results indicated that selective stent placement should be considered as the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…This device has been shown to have good MR imaging behaviour; however, this approach has not been used for coronary stents, most likely because the material would be too radio-opaque -even for X-ray fluoroscopy. The tantalum peripheral devices described earlier [40,41] also had reduced susceptibility artefact but this was purely incidental. While these stents became obsolete for design reasons, use of pure tantalum did not successfully carry through to newer coronary designs, due to lack of mechanical property optimization and also as the high radio-opacity would again be unsuitable for smaller stent sizes.…”
Section: Stent Materials For Alternative Imaging Compatibilitymentioning
confidence: 95%
“…Such material developments have indeed been fewer than the efforts to increase strength and radio-opacity, but this is understandable given the more tentative nature of any potential benefit and the investment already going into higher-strength and radio-opacity needs. Tantalum was explored early during stent development and was used in both the coronary Wiktor stent (Medtronic Inc., Minneapolis, MN) [40] and the peripheral Strecker stent (Boston Scientific Corp., Natick, MA) [41]. These were helical wound wire and knitted wire structures, respectively.…”
Section: Alternative Stent Materials For Improved Vascular Compatibilitymentioning
confidence: 99%
“…Tantalum has been used in the past with some degree of success for both the Wiktor coronary stent (Vaishnav et al, 1994) and the Strecker peripheral stent (Long et al, 1995). However, the possibility of Ta alloy development was ruled out as it was considered that the high density of the material would result in excessive radiopacity when imaged Having selected niobium as the platform for alloy development, some commercial compositions were initially assessed.…”
Section: Alloy Design Rationalementioning
confidence: 99%